@Calvin Lin
–
I meant that \(x \leq y\) if \(y \geq 1\) and \(x+y \leq 2\) if \(y \leq 1\). The reason the inequality holds is because x^3>y^3 due to our assumption.

@Brilliant Member
–
What you meant, is very different from what (you think) you wrote.

Given that your solution has numerous issues, I advise you to rewrite it from the start so that it can be clearly understood, instead of having others guess at what the missing steps are.

## Comments

Sort by:

TopNewestHint:Prove that \( x^4 + y^4 \leq x^3 + y^3 \leq x^2 + y^2 \leq x^1 + y^1 \leq x^0 + y^0 = 2 \).Log in to reply

@Svatejas Shivakumar tbh i was given this problem but couldnt ind any solution well i guess just wrong problem thanks anyway

Log in to reply

@Svatejas Shivakumar can this be proven \(x^{3}+y^{3}\leq 2\) for \(x^{3}+y^{3}\geq x^{3}+y^{4}\)

Log in to reply

I think that you mean \(x^3+y^3 \geq x^4+y^4\) instead of \(x^3+y^3 \geq x^3+y^4\) for \(x+y \leq 2\).

The converse is not true. For a counterexample, take \(x=1.5\) and \(y=0.5\).

Log in to reply

Let's assume WLOG, that \(x \ge y\).

We have \(x^3(x-1)+y^3(y-1) \leq 0\). So, \(x \leq 1\).

By Muirhead's inequality, \(x^4+y^4 \leq x^3+y^3 \leq x^3y+xy^3\) so \(x^3(y-1)+y^3(x-1) \leq 0\). So, \(y \leq 1\).

We know that \(a^3 \leq a\) for a which are positive real numbers.

So, \(x^3+y^3 \leq x+y \leq 2\).

Log in to reply

It is not true that \( x \leq 1 \). As a counter example, \( 1.01^3 + 0.9^3 \approx 1.76 > 1.01^4 + 0.9^4 \approx 1.70\)

Do you see the error in your reasoning? Hint: What is the sign of \( y - 1 \)?

Note: It is also not true that \( a^ 3 \leq a \) for positive real numbers, but that wasn't what you intended to say.

Log in to reply

I accidentally posted another incomplete solution but I am not able to edit it. I am also not able to delete this solution.

Log in to reply

We are working on fixing the "unable to edit / delete comment" bug.

Log in to reply

Yes I forgot to take the sign of y-1.

We must have \(x-1 \leq |y-1|\). Solving we get \(x \leq y\)(false due to our assumption) or \(x+y \leq 2\).

The answer follows.

In fact, the second inequality is not required.

Log in to reply

Log in to reply

Log in to reply

Given that your solution has numerous issues, I advise you to rewrite it from the start so that it can be clearly understood, instead of having others guess at what the missing steps are.

Log in to reply

thank you very much what about the \(x^{3}+y^{3}\geq x^{3}+y^{4}\)

Log in to reply